Neuroprotective effects of resveratrol in Alzheimer disease pathology - Rege, Shraddha D.; Geetha, Thangiah; Griffin, Gerald D.; Broderick, Tom L.; Babu, Jeganathan Ramesh (Frontiers in Aging Neuroscience, 2014)
Alzheimer’s disease (AD) is a chronic neurodegenerative disorder characterized by a progressive loss of cognitive and behavioral abilities. Extracellular senile plaques and intracellular neurofibrillary tangles are hallmarks of AD. Researchers aim to analyze the molecular mechanisms underlying AD pathogenesis; however, the therapeutic options available to treat this disease are inadequate. In the past few years, several studies have reported interesting insights about the neuroprotective properties of the polyphenolic compound resveratrol (3, 5, 4’-trihydroxy-trans-stilbene) when used with in vitro and in vivo models of AD. The aim of this review is to focus on the neuroprotective and antioxidant effects of resveratrol on AD and its multiple potential mechanisms of action. In addition, because the naturally occurring forms of resveratrol have a very limited half-life in plasma, a description of potential analogues aimed at increasing bioavailability in plasma is also discussed.